Antimicrobial activity of a biosurfactant produced by Bacillus licheniformis strain M104 grown on whey - Eman Zakaria Gomaa (Brazilian Archives of Biology and Technology, 2013)
The aim of the present study was to investigate the antimicrobial effect of the lipopeptide biosurfactants produced by Bacillus licheniformis strain M104 grown on whey. The biosurfactant was investigated for potential antimicrobial activity by using the disc-diffusion method against different Gram-positive bacteria {B subtilis, B. thuringiensis (two strains), B. cereus, Staphylococcus aureus (two strains) and Listeria monocytogenes)}, Gram-negative bacteria {(Pseudomonas aeruginosa, Escherichia coli (two strains), Salmonella typhimurium, Proteous vulgaris and Klebsiella pneumoniae) and a yeast (Candida albicans)}. The biosurfactant showed profoundly distinct antibacterial activity toward tested bacteria and displayed an antifungal activity against the tested yeast. Maximum antimicrobial activity of the biosurfactant was shown against S. aureus ATCC 25928. The biosurfactant had a broad inhibition effect on intracellular components of S. aureus ATCC 25928. The antimicrobial effect of lipopeptide biosurfactant produced by B. licheniformis strain M104 was time and concentration dependent. When biosurfactant was added to S. aureus medium in a concentration of (48 μg / ml), the maximum reduction of acid soluble phosphorous (53.06 %), total lipid (90.47 %) total proteins (53.43%), RNA (83.29 %) and DNA (48.50%) were recorded after 12 h of incubation period. From the preliminary characterization results, it could be concluded that biosurfactants were a suitable alternative in potential applications of medical fields.